Valor nutricional do farelo de arroz integral para frangos de corte de crescimento lento - GASPARINI, Sandra Paula (2014)
Two experiments to determine the metabolizable energy in different ages and true digestibility of amino acids of rice bran (RB), broiler slow growth were performed. In the first experiment, 352 birds were distributed in a completely randomized design with three treatments and six replicates of eight or six birds per experimental unit as experimental age. The RB replaced 40% references diets formulated for three age groups (1-30, 31-60 and 61-90 days). The method used was the total collection and 1.0% iron oxide was used as a fecal marker. In the second experiment, 168 birds at 41 days of age fed a diet free of protein (DFP) and formulated with 55% of RB as the sole source of dietary crude protein and amino acids were used. All birds were killed by cervical dislocation and open the abdominal cavity to collect the contents at the terminal ileum portion. The samples were sent for amino acid analysis using HPLC. Was used 0.5% of chromic oxide as a marker for determining the digestibility of amino acids of the RB and the endogenous excretion of amino acids. The mineral content of the RB, with a value of 3.94%, below those content presented in the literature. The apparent metabolizable energy, true and true corrected for nitrogen balance, found for the RB in birds 70-79 days of age (2,801, 3,002 and 2,394 kcal / kg, respectively), statistically different (P <0.05) from values obtained with birds 40-49 days (2,415, 2,566 and 2,427 kcal / kg, respectively) and birds 10-19 days of age (2,131, 2,266 and 2,214 kcal / kg, respectively). The coefficients of apparent metabolism of dry matter (CMADM), with values of 65.80% (70 to 79 days), 59.20% (40 to 49 days) and 53.10% (10 to 19 days of age), statistically different (P <0.05). The coefficient of real gross energy metabolization corrected for nitrogen balance (CMVGEn), found in birds 70-79 days (56.40%), statistically different (P <0.05) of the value found in poultry 10 to 19 days of age (49.10%). Thus, in the formulation of rations, should be considered the differences in energy values of RB for young and adult birds, because the digestibility of dry matter and gross energy, increases with age. The average true digestibility of amino acids of the RB was 79.5%, as fed, where the methionine had the lowest coefficient of true digestibility, with a value of 78.12% and the highest arginine, with a value of 82.10 %. The true digestible values were 0.51% for lysine, 0.18% for methionine, 0.41% for methionine + cystine, 0.39% for threonine and 0.52% for valine.